Destruction of Serbian Churches and Monasteries in Kosovo and Metohija from 1999 till 2022: Cultural-Geographical Determinants - Medojević, Jovo M.; Milosavljević, Saša A. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The autonomous province of Kosovo and Metohija is a historical part of Old Serbia and the central area of the medieval Serbian state of the Nemanjić family, which makes it a historical-geographical and cultural-geographical area of enormous importance for the Republic of Serbia. At the same time, the Serbian Orthodox Church throughout its entire spiritual, historical and cultural existence in Kosovo and Metohija shares the fate of the Serbian people. The destruction of Serbian religious monuments in Kosovo and Metohija has been happening for centuries, so the continuity of the destruction of Serbian churches and monasteries can be traced from the 17th century to the present day. During the NATO intervention on the Federal Republic of Yugoslavia and on the territory of the Autonomous Province of Kosovo and Metohija, which lasted from March 24 to June 9, 1999, Albanian extremists devastated and demolished the largest number of Serbian sacral monuments. At the same time, the period at the end of the 20th century and the first two decades of the 21st century was marked by the cruel persecution of Serbs from Kosovo and Metohija and the devastation of the entire Serbian cultural heritage. By applying the methodology of cultural-geographic research and field research, the goal of the paper is to confirm and document all known cases of devastation and destruction of Serbian sacral heritage in Kosovo and Metohija from 1999 to 2022, which were committed by the Albanian extremists.
Keywords: cultural-geographic determinants; Serbia; Kosovo and Metohija; churches; monasteries; devastation of monuments